Modelling children’s Gear task strategy use with the Dynamic Overlapping Waves Model - de Bordes, Pieter F.; Boom, Jan; Schot, Willemijn D.; van den Heuvel-Panhuizen, Marja; Leseman, Paul P.M. (Cognitive development, 2019)
•The developmental sequence of strategy use of the gear task was confirmed with DOWM.•Children develop from using sensorimotor strategies to abstract strategies.•The behavioral repertoire of strategy-use on the gear task changes microgenetically.•Sensorimotor experience seems crucial for developing abstract notions on STEM-topics. The Dynamic Overlapping Waves Model (DOWM) can model strategy use in problem-solving tasks for strategies that can be construed as developmentally and hierarchically ordered (Boom, 2015). We observed children’s (Mage = 11 years, SD = 6 months) strategy use during a task in which they had to find the rotation direction of the last gear in a series of connected gear chains, given the rotation direction of the first gear. Using DOWM, we found that strategy use was ordered as expected, from unskilled sensorimotor strategies to abstract strategies, and from less to more efficient in terms of speed and accuracy. This order aligns with the idea that perceptual learning is central to the emergence of abstract conceptual knowledge. Moreover, the current study shows that the DOWM does not preclude forward and backward transitions and even occasional transitions that skip certain strategies in the ordering. The DOWM seems a promising tool to developmentally capture the breadth of behavioral repertoire children display when they adopt new strategies for various problem-solving tasks.